CORRELAÇÃO ENTRE FASES DE ALFABETIZAÇÃO SEGUNDO ABORDAGEM CONSTRUTIVISTA E IDADES DE ESCOLARES INICIAIS - Meire Aparecida Judai; Maria Salete Vaceli Quintilio; Ana Carolina Oliveira Lima (Colloquium Humanarum, 2013)
According to the Constructivist school, to have a meaning, the literacy must occur in an interactive process, always followed by the children context and the reality they live. Stories and children´s interventions must be worked, and during the graphic moment, letters or words could agglutinate, be inserted, missed out, since they make some sense to them. Because the constructivist approach is adopted by most of the schools, and the large number of students with difficulties in learning that are treated in the speech therapist clinics, the present study had as objective to observe the steps in the literacy of 1st Elementary school year, and verify the literacy levels in public and private schools in Presidente Prudente - SP, Brazil. The samples were made by 41 children, 15 from private school and 26 from public school, between 5 and 6 years old. The used method was a dictation of words, which resulted in the Literacy Levels Classification. The Private School had the Level 4 grade (syllabic), while the Public School was between the Level 2 and 3 (syllabic-alphabetic and syllabic), on average. Therefore, it can be inferred that the private school had a better performance, considering the levels of literacy and the observation period of the sample, and that the children of this school have a performance for learning reading and writing rather than the Public School children evaluated.